2012
DOI: 10.1021/cm203502s
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Oxygen Ion Diffusion in Layered PrBaCo2O5+δ

Abstract: Oxygen diffusion and surface exchange coefficients have been measured on polycrystalline samples of the double perovskite oxide PrBaCo2O5+δ by the isotope exchange depth profile method, using a time-of-flight SIMS instrument. The measured diffusion coefficients show an activation energy of 1.02 eV, as compared to 0.89 eV for the surface exchange coefficients in the temperature range from 300 to 670 °C. Inhomogeneity was observed in the distribution of the oxygen-18 isotopic fraction from grain to grain in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
122
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(137 citation statements)
references
References 24 publications
14
122
1
Order By: Relevance
“…Fig. 1 shows the XRD patterns of as-prepared PB x CO (x ¼ 0.90e1.0) powder at room temperature, indexed to an orthorhombic superstructure with doubled c-axis, as a z a p , b z a p , c z 2a p (a p : the cell parameter of the primitive perovskite), which is consistent with Kilner's reports [12]. The XRD patterns of PB x CO collected at room temperature are correctly refined in the Pmmm space group (S. G.) derived from PBCO.…”
Section: Structure Analysis and Chemical Compatibilitysupporting
confidence: 85%
“…Fig. 1 shows the XRD patterns of as-prepared PB x CO (x ¼ 0.90e1.0) powder at room temperature, indexed to an orthorhombic superstructure with doubled c-axis, as a z a p , b z a p , c z 2a p (a p : the cell parameter of the primitive perovskite), which is consistent with Kilner's reports [12]. The XRD patterns of PB x CO collected at room temperature are correctly refined in the Pmmm space group (S. G.) derived from PBCO.…”
Section: Structure Analysis and Chemical Compatibilitysupporting
confidence: 85%
“…Indeed, exactly this mechanism has been visualized by in-situ high-temperature neutron powder diffraction studies [19]. Notice also that the activation energy E a for oxygen tracer diffusion coefficient D* is found to be about 98.4 kJ/mol [43]. This value is somewhat smaller compared to the obtained disordering enthalpy 127 kJ/mol for reaction (1), Table 2.…”
Section: Resultsmentioning
confidence: 55%
“…This value is somewhat smaller compared to the obtained disordering enthalpy 127 kJ/mol for reaction (1), Table 2. The difference can be explained as due to lower temperature range (below 700°С) used in [43] where according to our calculations the concentration of oxygen vacancies V O2 in PrBaCo 2 O 5+δ is negligibly small. Therefore, the probability for the O3 oxygen ion to have a neighboring vacancy V O2 available for O3-O2 jump is to be very small also.…”
Section: Resultsmentioning
confidence: 61%
“…5,6 Presently, there are numerous candidate oxides which are considered for cathode and electrolyte applications for the next generation of intermediate temperature solid oxide fuel cells. [7][8][9][10][11][12] In previous studies of reduced CeO 2 , 13 charge transport was demonstrated to be achieved by a hopping process of O vacancies and the related distortions. This mechanism is in agreement with the O defect model established by careful measurements of the electrical conductivity of reduced CeO 2 as a function of temperature and O 2 pressure in Ref.…”
Section: Introductionmentioning
confidence: 98%